EFEK MODERASI GAYA KEPEMIMPINAN PADA PENGARUH KEPUASAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL - Paryanto, MD. Rahadhini & (Universitas Slamet Riyadi, 2006)
ABSTRACT The research was undertaken within one month, namely within March 2006. The data sources are primary and secondary data. The data collecting method was using questionnaire. The sampling method was using proportional random sampling technique. The data analisys is done employing hierarchical regression, t and F test statistic, determination coefficient and, classical assumption tests. The research concludes that: 1) there is a significant effect of working satisfaction on Dinas Dikpora of Surakarta Municipal government officers’ performance. It is demonstrated with the t statistics on both regressions analysis employed in the hierarchical regressions, where p < 0.05; 2) the hypothesis stated that leadership behaviour strengthen the effect of working satisfaction on Dinas Dikpora of Surakarta Municipal government officers’ performance is not proved. It is demonstrated by the regression analysis of the F statistic tests on both regressions employed. The constant parameter in the first regression shows the value of 17.210, whereas the second regressions show the negative value of -97.649. It shows that leadership behaviour weaken the effect of working satisfaction on Dinas Dikpora of Surakarta Municipal government officers’ performance. Keywords: working satisfaction, leadership behaviour, officers’ performance.